Improbable women : five who explored the Middle East - Cotterman, William W. (Contemporary issues in the Middle East., 2013)
"Zenobia was the third-century Syrian queen who rebelled against Roman rule. Before Emperor Aurelian prevailed against her forces, she had seized almost one-third of the Roman Empire. Today, her legend attracts thousands of visitors to her capital, Palmyra, one of the great ruined cities of the ancient world